Pengaruh Interval training Rasio 1:2 dengan Rasio 1:3 Terhadap Daya Tahan Aerobik Pemain Sepak bola SMA Negeri 1 Turen - Ulum, Choirul; Yunus, Moch. (Universitas Negeri Malang, 2020)
Abstract: The purpose of this study was to determine anthropometric analysis and dominant physical conditions in male basketball players at SMK Telkom Malang. The research method used is the survey The purpose of this study was to find out significant differences in the effect of interval training ratio 1: 2 and interval training ratio 1: 3 on aerobic endurance. This study used a pre-experimental research design, namely pretest and posttest design in two groups. The subjects in this study amount to 30 football players of special talent class football players at SMA Negeri 1 Turen, which were divided into two groups using the ordinal pairing technique. This research was conducted for 18 meetings with a frequency of 3 times a week. The instrument in this test uses the multistage fitness test / bleep test. From results of the independent t-test is 0.801> 0.05. Based on the results of the analysis it can be concluded that there is no significant effect between interval training ratio 1: 2 and interval training ratio 1: 3.Â Keywords: Interval training Ratio 1:2, Interval training Ratio 1:3, Aerobic EnduranceÂ Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui mengetahui apakah ada perbedaan pengaruh yang signifikan antara interval training rasio 1:2 dan interval training rasio 1:3 terhadap daya tahan aerobik. Penelitian ini menggunakan rancangan penelitian pra-eksperimental yaitu rancangan pretest dan posttest dalam dua kelompok. Subjek dalam penelitian ini berjumlah 30 pemain sepak bola kelas BI (Bakat Istimewa) SMA Negeri 1 Turen yang dibagi menjadi dua kelompok menggunakan teknik ordinal pairing. Penelitian ini dilakukan selama 18 kali pertemuan dengan frekuensi 3 kali seminggu. Instrumen dalam tes ini menggunakan multistage fitness test/bleep test. Dari hasil uji independet t-test adalah 0,801>0,05. Berdasarkan hasil analisis tersebut dapat disimpulkan bahwa tidak ada pengaruh yang signifikan antara interval training rasio 1:2 dan interval training rasio 1:3.Â Kata kunci: Interval training Rasio1:2, Interval training Rasio 1:3, Daya Tahan Aerobik